Impact of fertilization depth on sunflower yield and nitrogen utilization: a perspective on soil nutrient and root system compatibility - Ren, Wenhao; Li, Xianyue; Liu, Tingxi; Chen, Ning; Xin, Maoxin; Liu, Bin; Qi, Qian; Li, Gendong (Frontiers in Plant Science, 2024)
The depth of fertilizer application significantly influences soil nitrate concentration (SNC), sunflower root length density (RLD), sunflower nitrogen uptake (SNU), and yield. However, current studies cannot precisely capture subtle nutrient variations between soil layers and their complex relationships with root growth. They also struggle to assess the impact of different fertilizer application depths on sunflower root development and distribution as well as their response to the spatial and temporal distribution of nutrients. The APSIM model was employed to explore the spatial and temporal patterns of nitrogen distribution in the soil at three controlled-release fertilizer (CRF) placement depths: 5, 15, and 25 cm. This study investigated the characteristics of the root system regarding nitrogen absorption and utilization and analyzed their correlation with grain yield formation. Furthermore, this study introduced the modified Jaccard index to analyze soil-root interactions, providing a deeper insight into how changes in CRF placement depth affect crop growth and nitrogen uptake efficiency. These results indicated that a 15 cm fertilization depth maximized the sunflower yield and nitrogen absorption. This depth promoted a greater RLD, promoting deeper root growth and improved nitrogen absorption. In contrast, shallow fertilization led to higher nitrate concentrations in the topsoil, whereas deeper fertilization increased nitrate concentrations in the deeper soil layers. These results could provide valuable insights for precision agriculture and sustainable soil management, highlighting the importance of optimizing root nitrogen absorption through tailored fertilization strategies to enhance crop production efficiency and minimize environmental impact.